A girl with intragenic variants in MARS2 and a chondrodysplasia phenotype - Hiroyuki Iijima; Yuko Tsujioka; Yoshiyuki Tsutsumi; Gen Nishimura; Yasushi Okazaki; Kei Murayama; Mitsuru Kubota; Akira Ohtake (Molecular Genetics and Metabolism Reports)
Background: The human mitochondrial methionyl-tRNA is crucial for mitochondrial translation, serving as both initiator and elongator in polypeptide chains. The MARS2 gene is responsible for binding methionine to mitochondrial tRNA. The clinical characteristics of MARS2 intragenic variants are still largely unknown, since only a pair of siblings has been reported. The present patient presented with psychomotor developmental delay, growth failure, and spondylar dysplasia, which attracted attention in infancy and deteriorated with age. Case presentation: A 7-month-old Japanese girl presented with failure to thrive, feeding difficulties, and psychomotor developmental delay. Radiological examination showed generalized skeletal alterations including mild spondylar dysplasia and abnormal ilia, which resembled mucopolysaccharidosis; however, the urinary glycosaminoglycan levels and alpha-L-iduronidase activity in the filter paper blood were normal. At age 33 months, she showed hyperlactatemia, and genetic analysis showed compound heterozygous novel variants (NM_138395.4: c.[277G > A]; [409C > T]: p.([Asp93Asn]; [Arg137Cys])) in the MARS2 gene. After starting vitamin supplementation, her growth and development improved. Radiological examination at ages 2 and 4 years demonstrated a skeletal phenotype: platyspondyly with anterior beaking of the vertebral bodies; large proximal femoral epiphyses; and mild brachymesophalangy. The results of the mitochondrial respiratory chain activity examination using skin fibroblasts were within the normal range. Conclusion: The skeletal phenotype may be a syndromic component of this disorder associated with MARS2 intragenic variants.